Assessment of the efficacy of reduced-radiation noncontrast computed tomography scan compared with the standard noncontrast computed tomography scan for detecting urolithiasis: A prospective single-center study. (7th March 2023) - Aggarwal, Gaurav; Adhikary, Samiran Das
Abstract: Background: Noncontrast computed tomography (CT) scan of the kidneys, ureter and bladder is the standard investigative modality for diagnosing and following up patients with urolithiasis. With each scan, a patient receives radiation of 18–34 mGy. Dose considerations become pertinent because of a 10% lifetime incidence rate and higher than 50% risk of recurrence, necessitating repeated imaging in the lifetime of a stone former. Hence, this study aimed to assess the sensitivity of "reduced-radiation" CT imaging by altering scan settings to lower than the "standard" norms. Materials and methods: Altogether, 222 patients (255 "kidney-ureter" stone-bearing units or "renal units") with urolithiasis and patients undergoing CT for other reasons with incidental findings of renal/ureteric calculi between 2017 and 2019 were included. All patients were subjected to 3 sequential scans at tube current settings of 250 mA (CT-N/Standard), 100 mA (CT-100), and 50 mA (CT-50) at a constant voltage of 120 kV. Their clinicodemographic and radiological findings were recorded and assessed for significance. Results: Of the 255 renal units, 117 were between 30 and 44 years of age, 75% were men. Of the 255 patients, 178 (70.1%) reported a first stone episode and 77 had recurrence. Lower ureteric calculi were predominant (40.4%). All calculi were identified on CT-N; CT-100 failed to detect calculi in 1 patient, and CT-50 failed in 3 patients, where all calculi were <3 mm in size. Meanwhile, none were undetected among patients with obesity. The sensitivity was 99.61% for the CT-100 and 98.82% for the CT-50, which indicated a 2.5 and 5 times lower radiation and dose/length, respectively, than CT-N. Conclusions: The reduced-radiation CT scan is safe, sensitive, and accurate for the diagnosis and follow-up of patients with urolithiasis with significantly lower radiation exposures. Our study lays the foundation to accept low-dose CT in general and CT-50 in particular, as the new "standard of care, " and attempt further dose reduction without loss of diagnostic efficacy.